A Coupling Error Compensation Approach Concerning Constrained Space Coordinate Precision of a Heavy-Load Longitudinal and Transversal Swing Table - Manxian Liu; Rui Bao; Shuo Li; Liang Ji; Suozhuang Li; Xiaoqiang Yan; Wei Li (Applied Sciences)
In this paper, an accurate error compensation method based on geometric parameter correction and process optimization is proposed for the problem of coupling error in a heavy-load longitudinal and transversal swing table (HLTST) under space constraints, which makes it difficult to control the position efficiently and accurately. The key geometric parameters of pitch and roll layers are determined according to the machining process and assembly relationship, and the kinematic model is modified to effectively reduce the impact of contour error on the system’s accuracy. A coupling error model is established and its transmission mechanism is analyzed to develop a positioning error compensation strategy. Numerical simulation is employed to examine the distribution law, sensitivity, and volatility of independent error and coupling error. This aids in optimizing the design of the table’s machining process by balancing machining accuracy and economy. After the identification of the error parameters, the error compensation model is verified using the uniform design experimentation. The experimental results demonstrate 96.94% and 65.63% reductions in absolute average errors for the pitch and roll angles, respectively, especially when the maximum positioning error under the maximum load condition is controlled within ±5%, which significantly enhances motion accuracy and robustness under complex working conditions. This provides theoretical support and practical guidance for real-world engineering applications.